2010
DOI: 10.1111/j.1460-2466.2010.01523.x
|View full text |Cite
|
Sign up to set email alerts
|

A Kernel of Truth? The Impact of Television Storylines Exploiting Myths About Organ Donation on the Public's Willingness to Donate

Abstract: In this study, 580 participants viewed one of the 30 full-length entertainment television episodes. Fifteen of these episodes centered on an organ donation storyline (ODS) where facts about the process were portrayed inaccurately; the remaining 15 were matched by program, but did not feature organ donation, and served as controls. Results indicated nondonors were significantly impacted by negative organ-donation-related content. ODSs produced more negative attitudes, less accurate knowledge, and perceptions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…An abbreviated version of Morgan et al's () organ donation attitude scale was used to measure participants' attitudes toward joining the organ donation registry. For example, “Joining the organ donation registry is a good thing for you to do.” The two‐item scale was reliably measured when used with registered (α = .80) and nonregistered (α = .81) organ donors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An abbreviated version of Morgan et al's () organ donation attitude scale was used to measure participants' attitudes toward joining the organ donation registry. For example, “Joining the organ donation registry is a good thing for you to do.” The two‐item scale was reliably measured when used with registered (α = .80) and nonregistered (α = .81) organ donors.…”
Section: Methodsmentioning
confidence: 99%
“…Although resistance toward registering as an organ donor remains (United Network for Organ Sharing (UNOS), ), recent work suggests that employing narratives is an effective strategy to mitigate resistance to promotional health messages (Moyer‐Gusé, ; Moyer‐Gusé & Nabi, ). More specifically, research has found that narratives reduce recipients' resistance to persuasive attempts when the audience becomes immersed in the storyline (Bilandzic & Busselle, ) and within the context of organ donation more specifically (Morgan, King, Smith, & Ivic, ). This study utilizes radio‐ad narratives to promote organ donation among both registered organ donors and adults not registered as organ donors.…”
mentioning
confidence: 99%
“…Supporters of organ donation have found that messages supporting donor registration compete against misinformation presented in the entertainment media (32)(33)(34)(35). Morgan and colleagues suggest that inaccurate portrayals in the US media result in misguided societal beliefs about organ donation and may influence individual's decisions to opt against becoming a donor (34). For example, this misinformation includes portrayals of a black market of stolen organs, morally corrupt transplant surgeons and untrustworthy organ allocation systems.…”
Section: Media Representations Of Substance Use Addiction and Organmentioning
confidence: 99%
“…For example, this misinformation includes portrayals of a black market of stolen organs, morally corrupt transplant surgeons and untrustworthy organ allocation systems. Some transplantation specialists have accused negative media representations of transplantation for contributing to changing public attitudes towards organ donation (34,(36)(37)(38). Morgan and colleagues argue that the donation myths perpetuated in the media should be replaced by "entertainment education" which is a health promotion technique that aims to improve public understanding of health behaviours (39).…”
Section: Media Representations Of Substance Use Addiction and Organmentioning
confidence: 99%
“…Despite its natural fit to the organ donation context, few studies have utilized message framing with the majority of studies examining advocacy frames within news or political contexts . In fact, the majority of message framing studies that have been conducted within the context of organ donation examine media framing in entertainment and news genres. By and large, these studies reveal that organ donation campaigners must work against the often‐negative portrayals of donation in entertainment media and relatively infrequent attention devoted to organ donation in the news .…”
mentioning
confidence: 99%